2011
DOI: 10.1177/000313481107701009
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Care Surgery Model Improves Timeliness of Care and Reduces Hospital Stay for Patients with Acute Cholecystitis

Abstract: In October 2009, an acute care surgery (ACS) model was implemented to facilitate urgent surgical consults. This study examines the impact of ACS on the timeliness of care and length of hospitalization for patients with acute cholecystitis. A retrospective cohort study was performed of patients presenting to the emergency department (ED) with acute cholecystitis who underwent early cholecystectomy. Patients with choledocholithiasis, pancreatitis, biliary colic, or cholelithiasis without cholecystitis were exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 16 publications
3
50
1
Order By: Relevance
“…Only one study reported a statistically significant reduction in perforation rate . All previous studies that assessed complication rates found statistically significant decreases in complication rate with the ACS model . None of the studies found statistically significant differences in negative appendicectomy rate .…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Only one study reported a statistically significant reduction in perforation rate . All previous studies that assessed complication rates found statistically significant decreases in complication rate with the ACS model . None of the studies found statistically significant differences in negative appendicectomy rate .…”
Section: Discussionmentioning
confidence: 86%
“…We were also disappointed to note that the introduction of an ACS model at our centre had not increased the proportion of appendicectomies performed by surgical trainees, rather than consultants or fellows (as determined by the primary operator on the operation record), as reported in prior studies examining the ACS model . We attributed this to the busy nature of work at our centre.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations